2021
DOI: 10.1002/acn3.51301
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral synucleinopathy in Parkinson disease with LRRK2 G2385R variants

Abstract: Objective Recent studies demonstrated cutaneous phosphorylated α synuclein (p‐syn) deposition in idiopathic and some monogenetic Parkinson disease (PD) patients, suggesting synucleinopathy identical to that in the brain. Although the LRRK2 Gly2385Arg (G2385R) variant is a common PD risk factor in the Chinese population, the pathogenesis of PD with G2385R variant has not been reported. We investigated whether synucleinopathy and small fiber neuropathy (SFN) are associated with the G2385R variant. Methods We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Yang et al 23 recently reported that patients carrying the LRRK2 risk variant G2385R have phosphorylated α‐syn deposition in the skin similar to patients without the variant. This variant increases the risk for PD by about twofold and is present in about 2% of the East Asian population, according to the Genome Aggregation Database (gnomAD) v.2.1.1 24‐26 .…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al 23 recently reported that patients carrying the LRRK2 risk variant G2385R have phosphorylated α‐syn deposition in the skin similar to patients without the variant. This variant increases the risk for PD by about twofold and is present in about 2% of the East Asian population, according to the Genome Aggregation Database (gnomAD) v.2.1.1 24‐26 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Chinese population it may increase PD risk by nearly two-fold. 38 Both cellular and animal model studies have found that LRRK2 plays a role in kinase activity and may cause α-syn to be phosphorylated. 39 Kinase activity is elevated in individuals with Gly2019Ser or Ile2020Thr mutations, which cause PD via “gain‐of‐function” or hyperactivity of LRRK2 .…”
Section: Lrrk2 Gene Mutationsmentioning
confidence: 99%
“… 40 Compared with idiopathic PD (iPD) patients, patients with the LRRK2 G2385R variant require a larger levodopa equivalent dose and manifest a specific clinical profile including gait dysfunction and postural instability, motor fluctuations, fatigue, and rapid eye movement sleep behavior disorders. 38 …”
Section: Lrrk2 Gene Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous brain pathology is a feature of LRRK2 -linked PD 2 , 26 , 27 ; as such, knowing whether there is a correlation between LRRK2 variants in each domain and specific pathology is an important approach that will contribute to our understanding of the pathogenesis of LRRK2 -linked PD. Although a skin biopsy study reports that synucleinopathy is associated with LRRK2 G2385R 28 , no brain autopsy of PD with LRRK2 G2385R has been reported. Here, we report a PD case with LRRK2 G2385R wherein a typical diffuse Lewy body disease pathology with mild gliosis, possibly caused by increased LRRK2 kinase activity in the brain was observed.…”
Section: Introductionmentioning
confidence: 99%